The effect of combined Moringa oleifera and demineralized freeze-dried bovine bone xenograft on the amount of osteoblast and osteoclast in the healing of tooth extraction socket of Cavia cobaya - Rostiny Rostiny; Eha Djulaeha; Nike Hendrijantini; Agus Pudijanto (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Alveolar bone has an important role in providing support to teeth and dentures. Loss of support caused by alveolar resorption will cause functional and aesthetic problems. Preservation socket using bone graft is one way to maintain the dimensions of the alveolar bone. Moringa oleifera leaf can increase the activity of bone graft in the formation of new bone. Purpose: This study was aimed to evaluate the effect of combined Moringa oleivera leaf extract and demineralized freeze-dried bovine bone xenograft (DFDBBX) towards the formation of osteoblasts and osteoclasts in the tooth extraction sockets of cavia cobaya. Method: This study used 28 cavia cobayas divided into four groups. The combination of Moringa oleifera leaf extract and DFDBBX was inducted into the sockets of lower incisor tooth with certain dose in each group, ointment 1 containing PEG (a mixture of PEG 400 and PEG 4000) for control group, ointment 2 containing Moringa oleifera leaf extract and DFDBBX and PEG (at active subtance consentration of 0.5%) for group 1, ointment 3 containing Moringa oleifera leaf extract and DFDBBX and PEG (at active substance concentration of 1%) for group 2, and Ointment 4 containing Moringa oleifera leaf extract and DFDBBX and PEG (at active substance consentration of 2%) for group 3. paraffin block preparations were made for histopathology examination using hematoxylin eosin staining. Result: The results showed that there were significant differences of the number of osteoblasts and osteoclasts in each treatment group (p <0.05). Conclusion: It can be concluded that the combination of Moringa oleifera leaf extract and DFDBBX at 2% cocentration can increase the number of osteoblasts and decrease osteoclasts in the healing of tooth extraction sockets of cavia cobaya.